ANALISIS SENTIMEN MASYARAKAT PADA MEDIA SOSIAL PLATFORM X TERHADAP PERTAMINA MENGGUNAKAN METODE DECISION TREE - Yksan Naibaho; Darwis Robinson Manalu; Samuel VB Manurung (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2026)
Platform X social media has become a platform for people to express their opinions, including on issues related to Pertamina. This study aims to analyze public sentiment on Platform X towards Pertamina using the ID3 (Iterative Dichotomiser 3) algorithm-based Decision Tree method. The data used are 2,005 tweets collected with the keyword "Pertamina Corruption". The data went through a preprocessing stage which includes case folding, tokenizing, stopword removal, and stemming. Text features were converted into binary representations (Binary Weighting) of 10 main keywords such as 'corruption', 'pertamina', and 'prosecutor'. The ID3 Decision Tree model was built recursively by selecting separator attributes based on the highest Information Gain value. The results showed that the built model had excellent performance. Evaluation on testing data (20% of the total data) produced an accuracy of 98.50%, with a precision value of 97.98%, a recall of 98.50%, and an F1-score of 98.22%. The 5-fold cross-validation results also confirmed the model's stability, with an average accuracy of 98.30% and a low standard deviation (0.0046). The contains_korupsi attribute was identified as the most informative root node in the decision tree structure. The conclusion of this study is that the Decision Tree method with the ID3 algorithm has proven effective and reliable in classifying public sentiment toward Pertamina on Platform X with high accuracy. The results of this analysis are expected to be used by Pertamina in understanding public opinion and formulating more appropriate communication strategies.